2011
DOI: 10.1002/jclp.20811
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of measures of therapeutic engagement in psychosocial and psychological treatment

Abstract: This article reports a systematic review of engagement measures for psychosocial therapy. MEDLINE, EMBASE, and PsycINFO databases were searched to identify English-language studies (published 1980 to February 2010) that reported on an instrument/rating scale to measure engagement in psychosocial treatment for mental health difficulties. Forty-seven studies were identified, reporting information on 40 measures of treatment engagement. Although our findings suggest that therapeutic engagement appears to be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 76 publications
1
76
0
2
Order By: Relevance
“…Na segunda parte, cada sessão do modelo adaptado foi avaliada quanto aos indicadores categóricos "Estrutura" (i.e., as sessões seguiram a estrutura básica), "Objetivos" (i.e., após a realização de cada sessão foi possível perceber que os objetivos propostos foram alcançados) e "Tarefas de casa" (i.e., as tarefas de casa propostas foram realizadas pelo participante) por meio de três opções de resposta: Sim (quando o indicador esteve presente), Em parte (quando o indicador esteve parcialmente presente) e Não (quando o indicador não esteve presente). A escolha e operacionalização dos indicadores utilizados foi baseada em estudos prévios (Dobson & Dobson, 2010;Tetley, Jinks, Huband, & Howells, 2011), bem como na consulta a duas psicólogas experts em TCC com crianças e adolescentes.…”
Section: Instrumentosunclassified
“…Na segunda parte, cada sessão do modelo adaptado foi avaliada quanto aos indicadores categóricos "Estrutura" (i.e., as sessões seguiram a estrutura básica), "Objetivos" (i.e., após a realização de cada sessão foi possível perceber que os objetivos propostos foram alcançados) e "Tarefas de casa" (i.e., as tarefas de casa propostas foram realizadas pelo participante) por meio de três opções de resposta: Sim (quando o indicador esteve presente), Em parte (quando o indicador esteve parcialmente presente) e Não (quando o indicador não esteve presente). A escolha e operacionalização dos indicadores utilizados foi baseada em estudos prévios (Dobson & Dobson, 2010;Tetley, Jinks, Huband, & Howells, 2011), bem como na consulta a duas psicólogas experts em TCC com crianças e adolescentes.…”
Section: Instrumentosunclassified
“…Two systematic reviews of measures on help seeking and treatment (Gulliver et al 2010) and treatment participation (Tetley et al 2011) are in the extant literature. Those reviews examine engagement as a universal construct, rather than as a culturally defined process.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in their systematic review, Tetley et al (2011) identified 40 measures assessing clients' behavioral engagement in treatment including session attendance, completion of treatment (within identified timeframe), completion of homework, client contribution such as self-disclosure or completing session activities, working alliance with the therapist, and helpful behavior in group therapies.…”
Section: Current Conceptualization and Assessment Of Engagementmentioning
confidence: 99%
“…In a systematic review of the engagement literature, Tetley, Jinks, Huband, and Howells (2011) noted that the concept of engagement is often construed as synonymous with client motivation, attitudes toward treatment, and the client's relationship with the therapist (the therapeutic alliance). In their view, engagement involves clients making an active and independent contribution to therapy.…”
Section: Therapeutic Engagementmentioning
confidence: 99%
“…They defined engagement as ''the extent to which the client actively participates in the treatment on offer'' (p. 928), and outlined six components of engagement: (1) attendance at sessions, (2) completion of treatment within the expected timeframe, (3) completion of expected homework betweensessions, (4) participating in the tasks of the therapy, (5) maintaining an appropriate therapeutic alliance with the therapist, and (6) being supportive towards other members of the group during group therapy. Client disengagement can lead to an ineffective use of services and poor treatment outcomes; it is for this reason that increasing client engagement has become a priority for mental health specialists (Tetley et al, 2011). Cunningham, Duffee, Huang, Steinke, and Naccarato (2009) noted that ratings by mental health care providers (MHCP) who are most familiar with the client's needs, abilities and motivation are the most commonly used measures of engagement.…”
Section: Therapeutic Engagementmentioning
confidence: 99%